Muscle hypertrophy in athlete training from a medical point of view - what do we know - Jan Biłogras; Katarzyna Kostelecka; Łukasz Bryliński; Marcin Wais; Dariusz Gruca; Konrad Warchoł (Kazimierz Wielki University, 2023)
Introduction Hypertrophy is the process of increasing the mass of a tissue. In this article, we focused on the impact of the mechanisms of muscle hypertrophy, its effect on the human body, correlation with the course of diseases and tolerance of treatment. We considered the benefits of having well-developed, and also touched on the problems of underdeveloped muscle mass. Results The main factors causing hypertrophy are resistance exercise training, mechanotransduction, metabolic pathways, ribosomal biogenesis, gene expression and the impact of hormones. The beneficial effect of high concentrations of testosterone and growth hormone, also IGF1, on skeletal muscle hypertrophy has been proven. On the other side, the studies have shown that high concentrations of glucocorticoids, such as cortisol are associated with reduced muscle mass. There are many positive aspects of a well-developed muscle mass such as an impact on the prognosis in  patients with cancers and sometimes reduces mortality among them. The problems of low muscle mass and sarcopenia are also mentioned. Low muscle mass can affect the poor prognosis of diseases such as cancer, hepatic cirrhosis and COVID-19. Postoperative complications are more common in patients with low muscle mass. One way to prevent this process may be to introduce resistance exercise training in patients struggling with problems of muscular atrophy. Conclusion Skeletal muscles have multiple functions in the human body. In addition to movement, they play a role in molecular processes like hormonal regulation. In addition, they can, when well developed, positively influence healing processes and the course of disease.